Practical communication theory - Adamy, David (SciTech Publishing, 2014)
The book is composed of the following topics: communication link; signal-to-noise ratio; antennas, link equation, receiver sensitivity; and radio propagation.
Includes index.
Keywords: Data transmission systems.; Signal theory (Telecommunication); Telecommunication systems.; elektronické knihy; electronic books